GENDER EQUITY IN AGRICULTURE - S. Yaqoob; A. M. Din; A. Saghir; A. Javed (Journal of Animal and Plant Sciences, 2006)
Gender rights, a global issue, touching the sensitive brains of thinkers, researchers and scientists of 21st century, whereas the role of women in all spheres of life is not comparable with the rights provided to them by the states and the societies as well. Although women participation in agriculture sector is remarkable but in return they are deprived of their basic rights. The present study was designed in Pakistan by selecting a tehsil of below poverty line district Attock. The sample drawn through simple random sampling technique and data were collected with the help of structured pre-tested interview schedule. The data were analyzed through a statistical package SPSS and arranged in tabular form. The results show the maximum participation of rural women in different sub-sectors of agriculture but further analysis reflected clear cut discrimination in land ownership, tenure, access to inputs, trainings, and credit facility. The finding of research study highlighted the immediate attention of Government, policy makers and law and order authorities to have a glance over such discrimination and reframe their rules and regulation, and mode of implementation.
Keywords: Gender; roles; rights; agriculture